Calculation and simulation of impedance diagrams of planar rectangular spiral coils for eddy current testing - Fava, Javier Oscar (2006)
The knowledge of analytical expressions for the electromagnetic (EM) fields produced by the coils used in eddy current testing is an importantpoint in the development and application of these devices. In the present work, the second order vector potential formulation is used for thecalculation of the fields produced by planar rectangular spiral coils of arbitrary number of turns and finite rectangular cross-section placed on aconducting half-space. Impedance plane diagrams are calculated for different frequencies, lift-off and half-space conductivity. Tests forconductivity assessment are also simulated. The theoretical results are compared with experimental measurements.